Correlation of hearing loss with various biochemical and disease parameters in patients with chronic kidney disease - Gautam, Dipendra; Paudel, D.; Thapa, S.; Sharma, S.K. (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Objectives: To correlate the hearing loss with duration of the disease, stage of the disease, ototoxic drugs use, co-morbidity and biochemical parameters in patients with chronic kidney disease (CKD). Material and Methods: This prospective study of 50 CKD patients was conducted in the department of ototolaryngology head and neck surgery and department of internal medicine, B. P. Koirala Institute of Health Sciences, Dharan, between December 2008 to November 2009. The blood investigation report of the patients were noted. Otological examination was carried out including tunning fork test and pure tone audiometry. Middle ear pathology and conductive hearing loss were excluded. Data was collected and analyzed. Results : Sensory neural hearing loss was higher in patients with; end stage renal disease (stage-5), co-morbidity, haemoglobin level less than 8.5, duration of CKD greater than 2 years, and ototoxic drug administration, but not statistically significant (P-value >0.05). Hearing loss in patients with CKD was not influenced by fasting blood sugar, serum urea, creatinine, sodium, potassium, calcium and serum phosphorus. (P-value >0.05) Conclusion: The hearing loss in patients with chronic kidney disease was not significantly related with stage of CKD, co-morbidity, ototoxic drug use, fasting blood sugar, serum urea, creatinine, sodium, potassium, calcium and serum phosphorus (P-value >0.05). The sensory neural hearing loss in these patients may be due to the advanced age and possible accelerated presbyacusis by the disease.